2020
DOI: 10.12659/msm.919302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Potential Regulatory Mechanisms of Serum Response Factor in 1118 Cases of Thyroid Cancer Based on Gene Chip and RNA-Sequencing Data

Abstract: Departmental sources Background:Thyroid cancer (TC) is one of the most prevalent endocrine malignancies and there may be many unclarified molecular events and gene types involved in TC. The objective of this study was to assess the clinical implications and potential mechanisms of serum response factor (SRF) in TC. Material/Methods:RNA-sequencing and gene chip data with TC expression were collected from The Cancer Genome Atlas/Genotype-Tissue Expression, Gene Expression Omnibus, ArrayExpress, Sequence Read Arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“… 49 Moreover, Jing et al found that miR-330-5p promotes thyroid cancer by inhibiting the expression of SRF gene tumor formation. 50 The miR-520e gene is located at locus 19q13.4 on the chromosome and is one of the critical members of the miR-520 family. The abnormal expression of miR-520e is closely related to the occurrence and development of various cancers, such as breast, liver, and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Moreover, Jing et al found that miR-330-5p promotes thyroid cancer by inhibiting the expression of SRF gene tumor formation. 50 The miR-520e gene is located at locus 19q13.4 on the chromosome and is one of the critical members of the miR-520 family. The abnormal expression of miR-520e is closely related to the occurrence and development of various cancers, such as breast, liver, and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This study included The Gene Expression Database (GEO) [ 24 ], ArrayExpress [ 25 ], Oncomine [ 26 ], and The Sequence Read Archive (SRA) [ 27 ] in order to search both Chinese and English medical literature for microarray data of BSG to analyze its clinical value in TC. Our search included data entered into the databases from the beginning to February 21, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…This study included The Gene Expression Database (GEO) [24], ArrayExpress [25], Oncomine [26], and the The Sequence Read Archive (SRA) [27] in order to search both Chinese and English medical literature for microarray data of BSG to analyze its clinical value in TC. Our search included data entered into the databases from the beginning to February 21, 2020.…”
Section: Bsg Expression In Tc Tissues From Other Microarray Datamentioning
confidence: 99%